Osteopontin, kidney injury molecule-1, and fetuin-A as prognostic markers of end-stage renal disease: A systematic review and meta-analysis - Yongki Welliam; Bendix Samarta Witarto; Visuddho Visuddho; Citrawati Dyah Kencono Wungu; Raden Mohammad Budiarto; Hendri Susilo; Chaq El Chaq Zamzam Multazam (PLoS ONE, 2025)
Background The global prevalence of chronic kidney disease (CKD) as a major renal disease is increasing rapidly. The progression of CKD may lead to end-stage renal disease (ESRD). Current diagnostic and prognostic methods still have some limitations. This study aims to evaluate the potential and predictive ability of Osteopontin (OPN), Kidney injury molecule-1 (KIM-1), and Fetuin-A on the incidence of ESRD in CKD patients. Methods A systematic review and meta-analysis were carried out based on the PRISMA guideline on registered databases for studies published up to December 21, 2023. The concentrations of each marker were then reported in pooled standardized mean difference (SMD) and hazard ratio (HR). Subgroup analysis was performed based on age, location, and KIM-1 specimen. Results We included 21 studies involving 15,983 patients. Meta-analysis revealed that increasing OPN (SMD = 5.52, 95% CI = 1.59–9.44, p = 0.01) and KIM-1 (SMD = 1.45, 95% CI = 0.50–2.39, p = 0.0027), as well as decreasing Fetuin-A level (SMD = -1.31, 95% CI = -2.37 – -0.26, p = 0.01) were significant in CKD patients with ESRD. Chronic kidney disease patients with increased KIM-1 levels showed 1.13 times increased risk of ESRD (HR = 1.13, 95% CI = 1.10–1.17, p <0.0001). Subgroup analysis showed that increased KIM-1 in urine or blood was strongly associated with ESRD, and decreased Fetuin-A levels in Asians had a significant association with the incidence of ESRD. Conclusion Osteopontin, KIM-1, and Fetuin-A significantly reflect ESRD in CKD patients, making them potential prognostic indicators.